A Case of Painless Legs and Moving Toes Syndrome in Parkinson's Disease Responsive to Dopaminergic Therapy. (28th August 2016) - Kawajiri, Sumihiro; Hoshino, Yasunobu; Nakamura, Ryota; Noda, Kazuyuki; Tomizawa, Yuji; Hattori, Nobutaka; Okuma, Yasuyuki
Abstract : Painless Legs and Moving Toes Syndrome (PoLMT) is a rare movement disorder characterized by flexion, extension, abduction, adduction, and torsion of toes without pain. It is considered a variant of Painful Legs and Moving Toes Syndrome (PLMT), which is characterized by similar movements but with pain. Although neuropathy and several central nervous system (CNS) involvements have been reported to be associated with PoLMT, the actual cause and mechanism remain unclear. Here we describe the first case of PoLMT in Parkinson's Disease (PD), parallel to parkinsonism in severity, who demonstrated a good response to dopaminergic therapy.